SPECTRUM OF OPTIC DISC CHANGES IN PRIMARY OPEN ANGLE GLAUCOMA - Iqbal, Sofia; Khan, Zubairullah; Khattak, Mushtaq Ahmad; Saeed, Nasir (Journal of Postgraduate Medical Institute, 2014)
Objective: To find out the patterns the optic disc changes associated withprimary open angle glaucoma (POAG). Methodology: This descriptive study was conducted at Ophthalmology department,Hayatabad Medical Complex Peshawar from 1st January to 31st December2009. All patients with diagnosed POAG, above the age of 30 years,having no lens or media opacity and ocular co-morbidity, were examinedthoroughly for patterns of optic disc changes associated with POAG. Frequenciesand percentages of the contour of neuroretinal rim, appearance of nervefiber layer, presence of optic disc hemorrhages, colour of optic nerve headwas noted. Descriptive statistics for disc were calculated for Vertical disc diameter(VDD), Cup/disc ratio (CDR), and Rim Disc Ratio (RDR). Results: Two hundred patients with POAG were included. Diffuse thinningand localized notching in the neuroretinal rim was noted in 188 (94%) and86 (43%) patients, respectively. Optic disc hemorrhage, Optic disc pallor andOptic disc atrophy was seen in 80 (40%), 127 (63.5%) and 15 (7.5%) cases,respectively.Mean VDD was 1.76mm in both right and left eyes. Mean vertical and horizontal CDR was 0.73 and 0.57 in the right and 0.765 and 0.611 in the left eye,respectively. Mean vertical and horizontal RDR was 0.451 and 0.543 in theright and 0.368 and 0.486 in the left eyes, respectively. Conclusion: Majority of the patients showed changes in measurements ofneuroretinal rim, so emphasis should be placed on the examination of neuroretinalrim in all patients of POAG.